PENGARUH EKUITAS MEREK JILBAB ZOYA TERHADAP NILAI PELANGGAN DI KOTA MATARAM - Ria Rosmalasari Sapitri (Universitas Bumigora, 2017)
This research entitle of the “Influence of Brand Equity of Zoya Hijab To Customer Valuein Mataram City” this research target is to know the assessment of customer at Mataram City for Brand Equity consist of Pervormance (X1), Social Image (X2), Value (X3), Trustworthiness (X4) and Commitment (X5) by product of Zoya hijab and to know the influence of Brand Equity of product of Zoya hijab to customer valui in Mataram city.This research represent the type of research of assosiatif eksploration, method of data collecting use is method of sample survey by meas of data collecting in the from of quetonaire alloted to 100 respondent people, with the technique of intake sample in the from of acidental sampling. Analyzer used is Multiple Linnar Regresion. The result of Multiple Linnar Regresion showed that Based of F test,can be known that Brand Equity variable consisting of Pervormance (X1), Social Image (X2), Value (X3), Trustworthiness (X4) and Commitment (X5) has significant influence by simultant to Customer Value (Y). And based of T test, can be known that Pervormance (X1), Social Image (X2), and Value (X3) has significant influence to Customer Value (Y) by partial. While the rest that consist of Trustworthiness (X4) and Commitment (X5) has not significant influence to Customer Value (Y) by partial.